THE ROLE OF ENTREPRENEURSHIP EDUCATION AND ATTITUDES IN SHAPING CAREER INTENTIONS AMONG ECONOMICS STUDENTS - Muadzah, Dzakira Athaya; Wibowo, Agus; Suparno (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study aims to understand the role of entrepreneurship education in shaping students’ attitudes, intentions, and career decisions to become entrepreneurs. Data were obtained from 133 students of the Faculty of Economics and Business at Universitas Negeri Jakarta who participated in the Wirausaha Merdeka Wira-Wiri program, out of a total of 339 distributed questionnaires. This research employed a quantitative method with a causal associative approach and Partial Least Square (PLS) analysis technique. The results show that entrepreneurship education has a direct influence on career choice and entrepreneurial attitude, but no direct effect on entrepreneurial intention. Entrepreneurial attitude affects intention. Entrepreneurial intention has a significant impact on the decision to pursue an entrepreneurial career. Furthermore, entrepreneurial attitude indirectly influences career choice through entrepreneurial intention.